Pengaruh Media Pendidikan Kesehatan Audiovisual Berbasis Self-Protection terhadap Tingkat Pengetahuan Siswa Kelas VII tentang Kekerasan Seksual di SMPN 10 Banjarmasin - Nazi Ratul Aulia; Suci Fitri Rahayu; Zaiyidah Fathony; Yurida Olviani (Yayasan Literasi Sains Indonesia, 2026)
Sexual violence against children and adolescents is a serious problem that affects physical, psychological, and social health. Early adolescents, particularly seventh-grade students, are in a vulnerable stage due to rapid developmental changes while still having limited knowledge of self-protection. A preliminary study at SMPN 10 Banjarmasin showed that most students did not adequately understand the definition and forms of sexual violence. Therefore, effective health education using media appropriate to adolescent characteristics is needed, one of which is self-protection-based audiovisual media. This study aimed to determine the effect of self-protection-based audiovisual health education media on the knowledge level of seventh-grade students about sexual violence at SMPN 10 Banjarmasin. This study used a quantitative method with a pre-experimental one-group pretest posttest design. The sample consisted of 61 seventh-grade students selected using purposive sampling. Data were collected using a questionnaire measuring knowledge of sexual violence before and after the intervention. Data analysis was conducted using univariate and bivariate analysis with the Wilcoxon Signed-Rank Test. The results showed an increase in students’ knowledge levels after receiving self-protection-based audiovisual health education, with a p-value < 0.001. Therefore, this media is recommended to be used as the health education methods in schools.